THE VOLATILITY OF GLOBALIZED FINANCIAL MARKETS: IMPACT ON THE STOCK EXCHANGE OF LIMA - PERU - Chambi Condori, Pedro Pablo (2017)
The study of the profitability´s volatility of the of international financial markets and its impact on the profitability of the Lima Stock Exchange is very important for the agents that take part in the markets: Stock market investors. The study of stationarity verification of the different stock markets´ profitability and the study of conditioned volatility is just as important for investors. According to the behavior showed through the indicators, the investors have a tool to qualify their decisions in the conformation of their portfolios of investment in risky financial assets. The objective of the investigation is to determine the type of profitability´s volatility of the LSE and the impacts it receives from the other global financial markets. The daily data has been collected by INDEX and later from the series, to obtain the daily profitability, and through the statistical processing of the collected data, the tests that have been used to determine the autoregressive model and conditioned by modeling heteroscedasticity ARCH (1) and GARCH (1,1) and the Dickey - Fuller test for unit root to qualify the stationarity of the series and on the other graphical and using the correlation matrix showing the incidences among various global financial markets.